The Role of Self-Esteem and Perceived Parental Mediation in Cyberbullying - Annisa Reginasari; Tina Afiatin; Hanif Akhtar (Faculty of Psychology, Universitas Gadjah Mada, 2021)
When access to information on the internet is expected to support the growth to adulthood, cyberbullying is instead becoming a threat to adolescents' psychological well-being. Parental mediation and self-esteem are considered as protective factors to youngsters from online risk. The present study examines whether self-esteem mediates the relationship between perceived parental mediation and cyberbullying. The study participants were 351 senior high school social students in Yogyakarta who are media and internet users. The data were collected using the Cyberbullying Scale (Cronbach’ α = 0.784), Self-Esteem Scale (Cronbach’ α = 0.766), and Perceived Parental Mediation Scale (Cronbach’ α = 0.656). Analysis using Structural Equation Modeling (SEM) showed that the proposed model was reached the goodness-of-fit ( = 53.711; df = 18; p = 0.001; RMSEA = 0.075; GFI= 0.964; CFI= 0.923). This study concluded that self-esteem partially mediated parental mediation and cyberbullying, with an indirect effect = -0.047 (p = 0.024; p<0.05). Self-esteem as the cognitive-personality factor and optimal parental mediation as environmental factors were considered to prevent adolescent cyberbullying. Therefore, we would recommend practitioners of educational, social, and clinical psychology to take the opportunity to involve self-esteem and parental mediation factors in intervention program design.